Human Enough: A Qualitative Study of Client Experience With Internet-Based Access to Pre-exposure Prophylaxis - Shana D Hughes; Kimberly A Koester; Edvard Engesaeth; Merissa V Hawkins; Robert M Grant (JMIR Publications, 2021)
BackgroundHIV pre-exposure prophylaxis (PrEP) is a way to prevent HIV infection using antiretroviral medications. However, common barriers to PrEP engagement include lack of access to prescribers; discomfort seeking sexual health services; and racism, homophobia, and transphobia in medical contexts. Key populations (eg, communities of color, young men who have sex with men, and transgender women) are underrepresented in terms of PrEP uptake in the United States. Nurx is an innovative company that has offered internet-based access to PrEP since 2016. ObjectiveIn this study, in partnership with Nurx, we aim to explore clients' experiences of digital PrEP access-including the difference made by the telehealth format-and to understand whether Nurx helped reduce barriers to PrEP. MethodsElectronic chart review and semistructured interviews were conducted with 31 PrEP requesters from California, Florida, Illinois, and New York. Interviews were recorded, transcribed, and subjected to inductive and deductive thematic analysis. ResultsSome interviewees reported initial skepticism about whether a web-based PrEP service could be legitimate or feasible. Despite this, most clients were effusive about their eventual Nurx experience, and many reported that Nurx eased barriers to PrEP access through the availability of knowledgeable, willing prescribers and minimizing embarrassment and discrimination. Our analysis suggests Nurx produced satisfaction by achieving an acceptable balance between 2 client desires: efficiency and humanity. Efficiency encompasses the simplicity, speed, and convenience of obtaining PrEP, both regarding the Nurx process itself and in comparison with in-person encounters. Humanity covers clients' wish for personalized, responsive interaction and a feeling of connection or care. Nurx's messaging platform was crucial to manifesting these qualities and was largely interpreted through the familiar frame of texting. Clients conceived efficiency and humanity as inversely related in a commercial enterprise and varied in the particular balance they felt was optimal. Those who wished for slightly more humanity than the service afforded used the concept of a trade-off to explain why Nurx remained appealing. ConclusionsOur findings augment evidence that internet-based PrEP provision can broaden access to this HIV prevention strategy. This important finding, notwithstanding a few provisos, merits mention. Telehealth, as practiced by Nurx, was still dependent on culturally competent medical providers as system inputs, and the very technology used to overcome access barriers (ie, the internet) generated new hurdles for some clients. Furthermore, clients did not interpret Nurx in a vacuum: their past experiences and the social and structural context mattered. Finally, only granular inquiry revealed precisely how Nurx satisfied clients whose experiences and preferences fell within a particular range. Extrapolating from this, we urge scholars not to fetishize technological solutions but rather to interrogate the ways in which any intervention's design works for certain kinds of patients.